Music and Drama Techniques to improve English language skills in fifth grades at a Public School (2017)
This research proposes improvement students’ English Language skills through the implementation of a pedagogical proposal training that integrates drama and music techniques to fifth graders. Special material was designed and implemented to carry out the effective training in which, techniques are thought of as existing along a continuum of possibilities between highly manipulative and very communicative tools where teachers are usually put into a less controlled role and students become free to be creative with their responses and interactions with other students. Brown (2006) and Clark (2013).